2019
DOI: 10.1111/obr.12977
|View full text |Cite
|
Sign up to set email alerts
|

Are long working hours associated with weight‐related outcomes? A meta‐analysis of observational studies

Abstract: The relationship between long working hours and body weight outcomes remains inconclusive; thus, we conducted a meta-analysis to assess the effect of long working hours on weight-related outcomes. PubMed and Embase databases were searched from their inception to June 2019. A random-effects model was used to assess the pooled odds ratio (OR) and corresponding confidence interval (CI). Subgroup analyses and sensitivity analyses were conducted to explore sources of heterogeneity. Publication bias was evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Among the eligible articles for inclusion in the selection process, 72 reviews with meta-analysis were included in our meta-review ( 14 85 ) ( figure 1 ). Supplementary table S3 presents the 27 excluded articles after fulltext reading and the reason for exclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the eligible articles for inclusion in the selection process, 72 reviews with meta-analysis were included in our meta-review ( 14 85 ) ( figure 1 ). Supplementary table S3 presents the 27 excluded articles after fulltext reading and the reason for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows the results for obesity. There were 2 literature reviews ( 42 , 85 ) and 3 IPD-Work consortium studies without literature review ( 58 , 59 , 77 ). Significant associations were observed between job strain and obesity using cross-sectional data but not using prospective data.…”
Section: Resultsmentioning
confidence: 99%
“…We used the random effects model to merge the data. The funnel chart was examined using Egger's and Begg's tests [23]. It indicated that there was a publication bias of p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the well-established risk for cardiovascular disease in individuals who work long hours, risks for various work-related metabolic diseases, such as obesity, hypertension, type 2 diabetes mellitus, and metabolic syndrome, have also been reported. Recently, Zhu et al reported that long working hours are associated with obesity-related harmful outcomes in their meta-analysis (17). Although these metabolic diseases are closely related to NAFLD, no previous studies have addressed the association between long working hours and NAFLD.…”
Section: Discussionmentioning
confidence: 99%